Pengaruh Brand Image dan Brand Trust terhadap Brand Loyalty melalui Customer Satisfaction sebagai Variabel Intervening Nike - Alexander, Gabriel; Widjaja, William (Reviu Akuntansi, Manajemen, dan Bisnis, 2024)
Purpose: This research is designed to investigate the impact of brand image, brand trust, and customer satisfaction as mediating variables on brand loyalty, specifically towards Nike in Jakarta and Tangerang. Research Methodology: The study employs a quantitative methodology, with data analysis conducted using SMARTPLS version 4. Sampling was achieved through Simple Random Sampling methods. Results: The results indicate that while brand image has a significant effect on brand loyalty, it does not significantly impact customer satisfaction. On the other hand, brand trust shows a substantial contribution to both brand loyalty and customer satisfaction. Additionally, customer satisfaction is established as having a significant influence on brand loyalty. In terms of the effect of brand image on brand loyalty, customer satisfaction is not a mediating factor. However, in the dynamics between brand trust and brand loyalty, customer satisfaction emerges as a key mediating factor. Limitation: The research was only conducted on 100 respondents, so the existing data does not yet cover the population of Nike consumers in Indonesia. Apart from that, the scope of the research is only as far as Jabodetabek and several other cities so that areas other than Jabodetabek have not received accurate data representation. Contribution: From the results of the research examined, the author wants to make a contribution to Nike as a research object: Nike must look for model innovation to get a unique model in the eyes of consumers. Nike must make their shoes trustworthy to consumers. Nike must be able to provide satisfaction to consumers when shopping for Nike shoes. Nike must be able to provide the right satisfaction so that their shoes are always worn by consumers.